Biochar in climate change mitigation - Lehmann, Johannes; Cowie, Annette; Masiello, Caroline A.; Kammann, Claudia; Woolf, Dominic; Amonette, James E.; Cayuela, Maria L.; Camps-Arbestain, Marta; Whitman, Thea (Nature geoscience, 2021)
Climate change mitigation not only requires reductions of greenhouse gas emissions, but also withdrawal of carbon dioxide (CO 2 ) from the atmosphere. Here we review the relationship between emissions reductions and CO 2 removal by biochar systems, which are based on pyrolysing biomass to produce biochar, used for soil application, and renewable bioenergy. Half of the emission reductions and the majority of CO 2 removal result from the one to two orders of magnitude longer persistence of biochar than the biomass it is made from. Globally, biochar systems could deliver emission reductions of 3.4–6.3 PgCO 2 e, half of which constitutes CO 2 removal. Relevant trade-offs exist between making and sequestering biochar in soil or producing more energy. Importantly, these trade-offs depend on what type of energy is replaced: relative to producing bioenergy, emissions of biochar systems increase by 3% when biochar replaces coal, whereas emissions decrease by 95% when biochar replaces renewable energy. The lack of a clear relationship between crop yield increases in response to fertilizer and to biochar additions suggests opportunities for biochar to increase crop yields where fertilizer alone is not effective, but also questions blanket recommendations based on known fertilizer responses. Locally specific decision support must recognize these relationships and trade-offs to establish carbon-trading mechanisms that facilitate a judicious implementation commensurate with climate change mitigation needs. Climate change mitigation strategies based on biochar generation—and its application to agricultural soils—can effectively sequester carbon, although biogeochemical and economic trade-offs must be considered.